Assessment on public external debt in Ethiopia - MENGSTE, Tegene Hailu (KDI School, 2022)
At early stage of economic development process, external borrowing is a means of fulfilling the resource gaps for the developing world. Nowadays, Ethiopia’s external debt to GDP is rising and continuously forcing the country to become among world's Heavily Indebted Poor Countries. This is serious problem coupled with covid-19 , Internal conflict and political uncertainties. The aim of the study is to assess the determinants of External debt of Ethiopia both in the long-run and short-run. The study applied ARDL co-integration model and secondary data covers from 1990 to 2019. In this study STATA statistical software package version-16 deployed and the necessary diagnosis tests have been conducted. The regression estimation result confirms that 88 per cent of the variation is explained within the model while 22 per cent is explained out of the model. The budget and trade deficit impart positive and statistically significant effect on external debt of Ethiopia. While debt service, inflation and openness have statistically significant and negative effects. However, economic growth has negatively and statistically insignificant effects. The result induces opening the economy to the rest of the world significant effect on reducing foreign debt burden. The policy implications are minimizing fiscal deficit by strengthening the tax system of the country; existing debt restructuring from business loan to concessional loan, which has lower interest rate, and properly managing inflation that contribute to the cost overrun of the country. All these efforts may reduce external debt in line with the capacity of the country in the future.
Thesis(Master) -- KDI School: Master of Public Management, 2022
Keywords: Debts, External--Ethiopia; Debts, Public--Ethiopia